KAJON casket for Filipino living under the poverty line - Apostol, Ma. Isabela Venezuela (College of Fine Arts, University of the Philippines Diliman, 2017)
Poverty here in the Philippines is one of the problems our government should really focus on and since the number of death is rising especially on the low income families, these two issues are mainly what the designer focused on. The purpose of this study is to create a unique casket designed for Filipino families living under the poverty line. The design is best described as a casket within a casket for it has two different containers wherein the external part is rental and the other part which is the internal casket is designed simpler and is the only one used for burial practices. The target market of the designer is for low income families, but since it is designed to show simplicity and elegance it can also be used by families for both different classes or social structure.